ANÁLISE E DIAGNÓSTICO DE UMA UNIDADE DE PRODUÇÃO FAMILIAR LEITEIRA, NO MUNICÍPIO DE BOA VISTA DO CADEADO - Krey, Daniela C.; Basso, Nilvo; Uhde, Leonir T.; Henriques, Angélica d. O.; Martins, Luciane R. V. (Salão do Conhecimento, 2013)
Resumo